Bcl-2 Analysis in Colorectal Carcinoma- An Immunohistochemical Study - Kumar K.T, Dr. Athulya Krishna; Saldanha, Dr. Prema (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Bcl-2 is an oncogene which inhibits apoptosis. The overexpression of Bcl-2 may play an important role in predicting the prognosis of colorectal cancer. Aim: To evaluate the expression of Bcl-2 oncoprotein with clinicopathological variables in colorectal carcinoma. Materials and Methods: Thirty resected specimens of colorectal carcinomas which included ten cases each of carcinomas in stages I, II and III were selected for the study. The Bcl-2 immunostaining pattern was correlated with the patient’s age, gender, site, size, grade, nodal status and pathological stage. Results: The age of the patients ranged from 18 to 75 years with 12 males and 18 females. The sizes of the tumours ranged from 1.5 to 9cms.Twelve cases were right sided and 18 cases were left sided. Twelve cases were low grade and 18 were high grade. Lymph nodes were positive in ten out of the thirty cases. Bcl-2 was positive in 56% of the cases. The Bcl-2 expression was 65% in stages I and II carcinomas and only 40% in stage III carcinomas. However, there was no statistically significant correlation with the clinicopathological variables. Conclusion: Analysis of Bcl-2 protein expression may have a potential use in the management of colorectal cancer.